2020
DOI: 10.1021/acsanm.0c02055
|View full text |Cite
|
Sign up to set email alerts
|

Graphene, the Swiss Army Knife of Nanomaterials Science

Abstract: Figure 1. Many uses of GBNs, with applications in environmental protection and remediation, separation technologies, sensing, biomedical diagnostics, catalysis, functional materials, electronic devices and processes, and finally energy-related technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 199 publications
0
5
0
1
Order By: Relevance
“…The integration of graphene and its derivatives has been previously documented [15][16][17][18][19][20][21]. Nevertheless, investigations on SPEs have been scarce in comparison, as most research focuses on modifying glassy carbon electrodes, with only a small number of studies concerning their application in the determination of other estrogens.…”
Section: Modifier/electrodementioning
confidence: 99%
“…The integration of graphene and its derivatives has been previously documented [15][16][17][18][19][20][21]. Nevertheless, investigations on SPEs have been scarce in comparison, as most research focuses on modifying glassy carbon electrodes, with only a small number of studies concerning their application in the determination of other estrogens.…”
Section: Modifier/electrodementioning
confidence: 99%
“…Since its discovery in 2004, graphene in both pristine and oxidized forms has been proposed for a wide variety of applications, ranging from nanocomposite material development to biomedical applications. This two-dimensional (2D) material’s unique combination of characteristics, such as a high surface-to-volume ratio, excellent electrical properties, chemical resistance, thermal stability, and solubility in aqueous solutions, makes graphene oxide (GO) of particular interest for biomedical applications including label-free biosensing and, more recently, as a drug delivery carrier. ,, For example, feasibility studies have shown that GO can be used as a drug carrier for the treatment of cancer, multiple sclerosis, and Alzheimer’s disease; in gene therapy; as an early disease-detecting biosensor for Parkinson’s disease, Alzheimer’s disease, and cancer; in glucose immunosensing; as a grafting composite for tissue engineering; and in cell imaging among other applications. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…Graphene (Gr) is well known for its high electrical and thermal conductivities, high optical transparency, and extremely high tensile strength . MoS 2 consists of one layer of molybdenum atoms sandwiched between two layers of sulfur atoms and exists in either a semiconducting phase (2H-MoS 2 ) or a metallic phase (1T-MoS 2 ). , 2H-MoS 2 is a direct band gap (1.9 eV) semiconductor, making it a great candidate for electronic, photonic energy harvesting, and photocatalysis applications. …”
Section: Introductionmentioning
confidence: 99%